Risk Factors Associated with Falls and Fractures Following Prescription of Opioids Among Privately Insured Patients with Osteoarthritis - Stuart Silverman; Patricia Schepman; J. Bradford Rice; Craig G. Beck; William Pajerowski; Alan G. White; Sheena Thakkar; Rebecca L. Robinson; Birol Emir (Journal of Health Economics and Outcomes Research)
**Background:** While prior research has shown that patients with osteoarthritis (OA) who are prescribed opioids have higher rates of falls and fractures following drug initiation, there is a limited body of work establishing a comprehensive model of factors that influence the risk of falls or fractures among these patients. **Objective:** Opioids are associated with negative clinical outcomes, including increased risk of falls and fractures. This study assessed the frequency, treatment characteristics, and risk factors associated with falls or fractures among patients with OA taking opioids. **Methods:** Optum Healthcare Solutions, Inc data (January 2012–March 2017) were used to identify patients over 18 with at least 2 diagnoses of hip and/or knee OA, and at least 90 days’ supply of opioids. Patients with cancer were excluded. Falls or fractures outcomes were assessed in the 36-month follow-up period after the date of the first opioid prescription after first OA diagnosis. Demographic, treatment, and clinical characteristics associated with falls or fractures were assessed using logistic regression. **Results:** Of 16 663 patients meeting inclusion criteria, 3886 (23%) had at least 1 fall or fracture during follow-up. Of these 3886 patients, 1349 (35%) had at least 1 fall with an average of 3 fall claims, and 3299 (85%) patients had at least 1 fracture with an average of 8 claims during follow-up. Spine (15.8%) and hip (12.5%) fractures were most common. Median time to fall or fracture was 18.6 and 13.9 months, respectively. Significant (_P_<.05) risk factors associated with at least 1 fall or fracture during the follow-up period included alcohol use (odds ratio [OR], 3.41), history of falling (OR, 2.19), non-tramadol opioid use (OR, 1.31), age (OR, 1.03), benzodiazepine use (OR, 1.21), and at least 1 osteoporosis diagnosis (OR, 2.06). **Discussion:** This study is among only a few that clearly identifies the substantial impact and frequency of falls and fractures associated with prescribing non-tramadol opioids to patients with OA. Findings suggest that fall or fracture risks need to be considered when managing OA pain with opioids. **Conclusion:** Falls and fractures impose a major clinical burden on patients prescribed opioids for OA-related pain management. Falls or fracture risks should be an important consideration in the ongoing treatment of patients with OA.